ANALISIS POTENSI JENIS POHON LOKAL GUNA REVEGETASI LAHAN TAMBANG EMAS (PT. J-Resources Bolaang Mongondow Site Lanut) - Henratno ., Pasambuna; Jailani ., Husein; Wiske ., Rotinsulu (Sam Ratulangi University, 2017)
The purposes of this study are (1) to know the local trees which growing at area before mining operation began and when mining operation by PT. J Resource Bolaang Mongondow has started, (2) to know the kind of local trees which is appropriate with revegetation land, (3) to know technical planning the use of local tree for revegetation gold mine area. This study is use line swath method. This method is as the modification of dual swaths method or track method which with through one or more swaths in the track so that in every line path should have many swaths in some distance. The sampling intensity which use in this study is 10 %. The variables (data) of the study are consists by primary data and secondary data. To collect the data the researcher use a literature study which to collect the first data from many literatures about the analysis of local trees and revegetation land, direct observation, and identify kind of local trees by using work sheet data. The result of the study at the PT. J Resources Bolaang Mongondow Lanut-Site forest area, the researcher have found that (1) 29 species of vegetation tree level with the total number 50 individual trees and vegetation of local trees consist of 8 species and those are Matoa (Pometia pinnata), kitchen wood (Dryobalanops aromatic), Gopasa (Vitex cofassus), Sengon (Albazia moluccana), Benuang (Octomeles sumatrana), Trembesi (Albizia saman), Candlenut (Aleurites moluccana), and Durian (Durio spp). From all of the total number of individual trees which is in 6 swaths examples (plot), (2) it has founded 10 species trees level with the level of dominance (level of mastery) in the vegetation community are: Diangow (Anarcadium Sp), Dongiat/Matoa (Pometia Pinnata), Dau’/Dao (Dracontomelon dao), Toraut/Gopasa (Vitex cofassus), Biluk (Aegle marmefes), Nutmeg (Myristica sp), Dongkat/Stone wood (Irvingia malayana oliv), Atul/Kitchen wood (Dryobalanops aromatic), Tagoy (Laportea sinuate), and tula-tula (Floribundus muel). (3) For the revegetation area planning should be formulated that the revegetation area in gold mine must effective and efficient, because the area with slope and difference contour will have different way to handling (land with <300 slope have different slope >300).